Challenges, Strategies, And Policies For The Empowerment Of Pakistani Women Farmers: A Qualitative Analysis With A Capability Approach - Dr. Umbreen Javaid (Migration Letters, 2024)
Women make up approximately 70 percent of the agricultural workforce in Pakistan, but their contributions are primarily unrecognized and undervalued. This study intends to explore challenges, strategies, and policies for empowering Pakistani rural farmers. The study was qualitative in nature by conducting face-to-face interviews with rural women of four districts of Punjab province, Pakistan. The participants were approached through personal contacts and a referral system (snowball sampling). Finally, fifteen interviews were conducted and data were analyzed using Nvivo Software. This study found that women were facing challenges related to education, learning and training, inheritance rights, financial empowerment, mobility, and freedom. They w[1]ere also facing some kind of domestic violence and had less access to justice. Providing equal educational and learning opportunities, access to property rights, and financial independence could help in strengthening empowerment among Pakistani rural women. The study drew policy implications related to gender equality, women’s empowerment through access to economic assets, education and employment, and encountering domestic violence.